Mechanisms Governing Interannual Variability of Stratosphere‐to‐Troposphere Ozone Transport. Issue 1 (12th January 2018) - Albers, John R.; Perlwitz, Judith; Butler, Amy H.; Birner, Thomas; Kiladis, George N.; Lawrence, Zachary D.; Manney, Gloria L.; Langford, Andrew O.; Dias, Juliana
Abstract: Factors governing the strength and frequency of stratospheric ozone intrusions over the Pacific‐North American region are considered for their role in modulating tropospheric ozone on interannual timescales. The strength of the association between two major modes of climate variability—the El Niño–Southern Oscillation (ENSO) and the Northern Annular Mode (NAM)—and the amount of ozone contained in stratospheric intrusions are tested in the context of two mechanisms that modulate stratosphere‐to‐troposphere transport (STT) of ozone: (StratVarO3 ) the winter season buildup of ozone abundances in the lowermost stratosphere (LMS) and (JetVar) Pacific jet and wave breaking variability during spring. In essence, StratVarO3 corresponds to variability in the amount of ozone per intrusion, while JetVar governs the frequency of intrusions. The resulting analysis, based on two different reanalysis products, suggests that StratVarO3 is more important than JetVar for driving interannual variations in STT of ozone over the Pacific‐North American region. In particular, the abundance of ozone in the LMS at the end of winter is shown to be a robust indicator of the amount of ozone that will be contained in stratospheric intrusions during the ensuing spring. Additionally, it is shown that the overall strength of the winter season stratospheric NAM is a useful predictor of ozone intrusion strength. The results also suggest a nuanced relationship between the phase of ENSO and STT of ozone. While ENSO‐related jet variability is associated with STT variability, it is wave breaking frequency rather than typical ENSO teleconnection patterns that is responsible for the ENSO‐STT relationship. Key Points: Stratospheric variability exerts a stronger influence on ozone intrusions than tropospheric jet variability Ozone intrusion frequency is more related to wave breaking frequency than it is to teleconnection patterns The strength of the winter stratospheric Northern Annular Mode is indicative of spring ozone intrusion strength